Ecological marketing and features of its application - G. A. Sadikhanova; B. B. Rysbaeva (Экономика: стратегия и практика)
The article is devoted to the study of new marketing strategies used in environmental marketing. Environmental issues appear in the press and are on the political agenda in many countries around the world. Society seeks to find a balance between the desire of all consumers to meet their needs and the desire to preserve their environment. In recent years, concerns about the impact of the manufacturing sector on the environment have affected not only governments and scientists, but also the public. He played a crucial role in the development of environmental marketing. Environmental marketing allows you to think through and develop the structure of the business survival system in the conditions of total market desire to create an eco-friendly environment. In the study, the authors point out that environmental marketing is one of the tools for creating conditions for sustainable development of society.